Batik Merbok: indulgence / Suzaini Azmin - Azmin, Suzaini (Universiti Teknologi MARA Cawangan Kedah Kampus Sungai Petani, 2007)
Batik Merbok design based on these motives: 1. Sanskrit writing 2. Paddy 3. Bricks 4. Zebra Dove 5. Wood Carving 6. Mangrove